Current developments in green finance - Lena Liebich; Lukas Nöh; Felix Rutkowski; Milena Schwarz (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2020)
The transformation of economies towards significantly reduced CO2 consumption raises high investment and capital requirements. Financial and capital markets can help to mobilize the necessary funds for global investment needs and to steer capital towards sustainable investments. Moreover, potential disruptive impacts of climate change on the financial system have started to become more apparent recently and require central banks, regulators and supervisors to take a conscious look at the risks and opportunities of climate change for financial intermediaries and markets. This article offers a comprehensive discussion on how green finance has been evolving thus far and explores the opportunities and key developments ahead with particular emphasis on four selected highly topical issues: 1) the introduction of German green government bonds, 2) obstacles to the correct pricing of climate-related risks, 3) the EU taxonomy that has recently been put forward to develop a uniform classification of sustainable economic activities as well as 4) the role of central banks in fostering the transition to a low-carbon economy.
Keywords: 330; Klimapolitik; Finanzierung; Klimawandel; Finanzsektor; Öffentliche Anleihe; Finanzmarkt; Risiko; Bewertung; Klassifikation; Geldpolitik; Zentralbank